A method for the preparation of intact chromosomal DNA of Pycnoporus cinnabarinus - V. CIFUENTES; C. Martinez; G. Pincheira (Fungal Genetics Reports, 1990)
We describe an improved procedure to obtain chromosomal DNA of Pycnoporus cinnabarinus, which was used in pulse field gel electrophoresis employing a contour-clamped homogenous electric field (CHEF). Four bands of chromosomal DNA were separated. The procedure may be useful to study the genome of other filamentous fungi.